2014
DOI: 10.3892/ol.2014.1881
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of epidermal growth factor receptor in locally advanced esophageal squamous cell carcinoma for patients receiving chemoradiotherapy

Abstract: The aim of the current study was to investigate the prognostic significance of epidermal growth factor receptor (EGFR) in patients with locally advanced esophageal squamous cell carcinoma (ESCC) receiving concurrent chemoradiotherapy (CCRT). In total, 47 patients with locally advanced ESCC who were treated with CCRT were included in the present study. The chemotherapeutics comprised of 5-fluorouracil (750–1,000 mg/m2/day; days one to five) and cisplatin (30 mg/m2/day; days one to three) in combination with rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Epidermal growth factor receptor (EGFR) is overexpressed in 59.6% to 76% of ESCCs 66,67 and is associated with a poor prognosis. 66,67 Large-scale sequencing studies have shown EGFR to be overexpressed (in 68% of tumors) and/or amplified (in 11%-24%) 62 but not frequently mutated (in 0-1.8% of ESCCs). [62][63][64] Moreover, 78.6% of ESCCs have mutations and/or amplifications in factors downstream of EGFR, such as RAS and AKT pathways.…”
Section: Epidermal Growth Factor Receptor Signaling Pathwaymentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is overexpressed in 59.6% to 76% of ESCCs 66,67 and is associated with a poor prognosis. 66,67 Large-scale sequencing studies have shown EGFR to be overexpressed (in 68% of tumors) and/or amplified (in 11%-24%) 62 but not frequently mutated (in 0-1.8% of ESCCs). [62][63][64] Moreover, 78.6% of ESCCs have mutations and/or amplifications in factors downstream of EGFR, such as RAS and AKT pathways.…”
Section: Epidermal Growth Factor Receptor Signaling Pathwaymentioning
confidence: 99%
“…The difference could have been due to the difference in the scoring method between the two series. In the communication of Gao et al [32] and that of Lin and the colleagues [19] both reported that there was no correlation between ESCC tumor differentiation and overexpression of EGFR with P-value of (.882 and .853) respectively. The importance of grade of tumor in EC and ESCC particularly, is controversial.…”
Section: Discussionmentioning
confidence: 98%
“…In the observations of Gao et al, EGFR overexpression was associated with poor survival in HNSCC patients receiving CCRT (19). Szabó et al examined expression and genetic alteration of EGFR gene by FISH with 71 HNSCC patients and observed that increased copy number and overexpression of the EGFR gene was associated with poor prognosis in HNSCC (20).…”
Section: Discussionmentioning
confidence: 99%